Editorial: Blockchain-driven business models - Horst Treiblmaier; Abderahman Rejeb; Teck Ming Tan; Guido Ongena (Digital Business, 2025)
In this editorial, we introduce the Special Issue on Blockchain-Driven Business Models. Over the last decade, academics have proposed numerous ideas on how to integrate the unique properties of blockchain, such as immutability, traceability, and programmability, into existing business models or to utilize them for developing startups from scratch. Practitioners have tried out countless disruptive business ideas, some of which have failed, while others have already begun to transform entire industries. This Special Issue explores the concept of blockchain-based business models from various angles, offering different theoretical perspectives and paving the way for future research in this groundbreaking area.
Keywords: 650; Blockchain; Business models